A regulação do registro de agrotóxicos em face da função eficacial do direito fundamental ao meio ambiente ecologicamente equilibrado - Santos, Amanda Farias Galvão (2021)
This master’s dissertation, submitted to the Graduate Program in Law of the Federal University of Rio Grande do Norte, analyzes the regulatory mechanisms of pesticide registration in Brazil facing the right to a ecologically balanced environment. Before the growing use of pesticides in Brazilian agriculture and quickly increase in the number of records of new active principles, the choice of topic is justified and acquires current relevance. From this perspective, the research has the general objective of analyze whether the Brazilian legal framework concerning the approval and registration of pesticides contributes to the achievement of the right to a ecologically balanced environment. In order to achieve this, have been determined as specific objectives: identify the legal content of the right to a ecologically balanced environment in the Federal Constitution of 1988 and make connections with the idea of sustainable development; understand the parameters that guide the regulation of pesticides in Brazil, especially with regards to the approval of the register of pesticides; investigate how the country is conducting its actions in order to implement the developmental function of the right to a ecologically balanced environment in the juridical treatment of that issue. As a methodology, the qualitative approach and the deductive method was used, as well as bibliographic and documentary search techniques for the collection of data. Finally, in view of the information gathered and the legal bases presented, it was concluded by the need to improve regulatory mechanisms and agrarian policy planning in order to reduce the risks of pesticides uses in Brazilian crops, avoid the uncontrolled use of these substances, encourage sustainable production models and implement the effective function of the right to the environment ecologically balanced.